Predicting Behavioral Problems in Students with Intellectual Disability Based on Maternal Acceptance and Resilience: The Mediating Role of Aggression - Jozari, Raziyeh; Moradi, Sajede; Khazraei, Forough; Taassob, Zahra; Behrooz, Raziyeh (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to predict behavioral problems in students with intellectual disabilities based on maternal acceptance and resilience, with the mediating role of aggression. The present study is descriptive in nature and was conducted using a correlational approach based on structural equation modeling. The statistical population consisted of all students with intellectual disabilities enrolled in special education schools under the Exceptional Education Organization in Shiraz during the 2023–2024 academic year. The sampling method was simple random selection, and a total of 127 students were chosen as the final sample. Among the final sample participants, 70.1% were boys, and 29.9% were girls. Data collection instruments included the Conners' Parent Rating Scale—Short Form for behavioral problems, the Connor-Davidson Resilience Scale (2003), the Acceptance and Action Questionnaire developed by Hayes, Baer, Carpenter, Gönül, Zettle, and colleagues (2011), and the Buss and Perry Aggression Questionnaire (1997). Data analysis was performed using SPSS version 16 and SmartPLS software. The study findings indicated a significant negative relationship between maternal acceptance and resilience and behavioral problems in students with intellectual disabilities. Additionally, these two variables significantly and negatively predicted behavioral problems in these students. Based on the findings, it can be inferred that early maternal acceptance and resilience can serve as predictive factors for behavioral problems in students with intellectual disabilities.Keywords: Resilience, Acceptance, Behavioral Problems, Intellectual Disability, Aggression